新穎塊材與奈米螢光體之製備與其在照明、生物影像檢測與綠能元件之應用探索 - 陳登銘; CHEN TENG-MING (My University, 2013)
本計畫為一基礎與應用並重的三年期研究，延續上一期(2009-2012)計畫，主要聚 焦於下列研究課題： 一、新穎照明用螢光體之合成、發光特性研究與應用與能量轉移之研究。特別是具備 高共價性主體且可吸收藍光之非氧化物。此外，發光顏色可調變之新穎螢光體且包含 Ce3+→Eu2+、Ce3+→Mn2+或Yb2+→Mn2+ 等共摻敏化劑/活化劑之可供探討能量轉移機制 的螢光體系統均在研究之範疇。 二、具生物窗口功能性奈米螢光體之製備與其在生物影像檢測之應用。特別是粒徑約 為10-200 nm 之Yb3+/Er3+、Yb3+/Tm3+、Yb3+/Ho3+或Yb3+/Pr3+共摻YF3,、YVO4、NaYF4 或 ROCl (R 為稀土)等具備近紅外激發近紅外放射稀土的奈米螢光粉之合成、特性鑑 定，並評估其在近紅外螢光生物影像偵測應用之潛力。 三、利用奈米上/下轉換稀土螢光粉/奈米結構以有效提升矽基太陽能電池轉換效率。 我們預期第一年將可研發出新穎高共價性發光二極體用的螢光體、功能性近紅外 發光與上/下轉換奈米螢光體之製程，並掌握製程參數，以確保化學合成之再現性與可 靠度，同時完成其晶相、發光、微結構、光譜學等特性量測、鑑定與分析。第二年則 進行上述螢光體發光性能與微結構之最佳化與奈米化，評估近紅外光螢光探針之製 作，並篩選目標活體與細胞進行生物影像偵測；另一方面則評估具備提升光伏電池光 電轉換效率之奈米螢光粉應用潛力。第三年將利用近紅外螢光生物影像技術，發展探 測生物深層組織影像的技術；另一方面則以新穎螢光粉試封裝白光發光二極體。

As a follow-up to the previous research, this investigation is a three-year long-term fundamental- and application-oriented research, which is attempted to develop novel highlycovalent non-oxide phosphors for solid-state lighting and nanophosphors for near-infrared (NIR) fluorescence bioimaging (FBI) and solar cells with enhanced conversion efficiency. We attempt to investigate the followings: (a) The preparation of novel highly-covalent non-oxide phosphors and investigation of their luminescence properties and applications in LED lighting. The phosphor systems that facilitate energy transfer of Ce3+→Eu2+, Ce3+→Mn2+ or Yb2+→Mn2+ in selected hosts will also be included to investigate the potential single-phased color-tunable phosphors and study the energy transfer mechanism. (b) The preparation and characterizations of NIR-NIR nanophosphors (size of 10-200 nm) with biological-window characteristics and compositions of Yb3+/Er3+, Yb3+/Tm3+, Yb3+/Ho3+, Yb3+/Pr3+-codoped YF3, YVO4, NaYF4 or ROCl (R: rare earths). With thorough characterizations on these materials, their potential applications in NIR-FBI will be evaluated. (c) The enhancement of conversion efficiency of nanophosphor-coated Si-based solar cells will be studied by utilizing spectral conversion technique and by integrating down- (or up-) shifting low-scattering nanophosphors into nanostructure of the solar cell surface. We anticipate to establish the synthetic methodology, secure processing parameters, and assure the reproducibility and reliability of the preparation of LED phosphors and the surfacefunctionalized NIR down- and up-shifting nanophosphors. The phase identification and characterizations and analysis of luminescence, microstructure, and spectroscopic properties will be simultaneously accomplished. In the second year, we will attempt to optimize the performance of synthesized LED phosphors. The fabrication of the NIR fluorescence probe and screening of biotargets for NIR-FBI studies will be evaluated and carried out. The effect of various nanophosphor coatings on the efficiency enhancement of solar cells will be also evaluated. In the third year, the NIR-NIR nano-materials synthesized and characterized and the NIR-FBI technique will be utilized to probe the image of various bio-targets, both in vivo and in vitro. The well-characterized highly-covalent non-oxide phosphors will be used to fabricate white-light LEDs and investigate the color rendering and chromaticity properties.
An Investigation on the Preparation of Novel Bulk and Nano Phosphors and Their Applications in Lighting, Bioassay, and Green Energy
Keywords: 稀土發光; 白光發光二極體; 能量轉移; 生物窗口; 近紅外螢光生物影像; 奈 米螢光體; 光譜轉換技術; 奈米結構; 矽基太陽能電池; Rare earth luminescence; White-light LED; Energy transfer; Biological window; Near-IR fluorescence bioimaging (NIR-FBI); Nanophosphors; Spectral conversion technique; Nano structure; Si-based solar cells